2005
DOI: 10.1007/s00244-003-0246-7
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Endocrine Disruption in a Sentinel Species (Chrysemys picta) on Cape Cod, Massachusetts

Abstract: Freshwater turtles (Chrysemys picta) were collected from two sites on Cape Cod, MA. One site (Moody Pond), adjacent to the Massachusetts Military Reservation (MMR), was considered potentially impacted by toxic agents deriving from contaminant point sources on the MMR. The second (reference) site (Washburn Pond), to the east of the MMR, was considered not impacted by these pollutants and was chosen as a control site. Plasma estradiol 17 beta and vitellogenin were significantly lower in female turtles from Moody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 31 publications
1
17
0
1
Order By: Relevance
“…Studies about mating systems (sperm storage and multiple paternity of nests) would be necessary in order to estimate the number of effective males in the population, to know their genetic diversity, its biological consequences, and to complete this information (Sanz et al, 2007). There is also no evidence of alterations in fertility of breeding sea turtles of both sexes due to environmental pollution (Van Look Kime, 2003;Ferber, 2005;Rie et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies about mating systems (sperm storage and multiple paternity of nests) would be necessary in order to estimate the number of effective males in the population, to know their genetic diversity, its biological consequences, and to complete this information (Sanz et al, 2007). There is also no evidence of alterations in fertility of breeding sea turtles of both sexes due to environmental pollution (Van Look Kime, 2003;Ferber, 2005;Rie et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the proportion of fertilized eggs of a clutch is a good estimator of male abundance and fertility as Rowe et al (2004) observed in freshwater turtles, of human female stress during mating (Campagne, 2006) or of physiological alterations of the sperm or ova, as detected by Rie et al (2005) in marine fishes. These factors may have a subsequent impact on hatching success.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, renal and hepatic Cd concentrations were higher than the toxic threshold established for freshwater painted turtles Chrysemys picta (Rie et al 2005). Despite marine turtles being considered organisms that accumulate higher Cd concentrations (Storelli et al 2005) than freshwater turtles and terrestrial vertebrates, it is possible that toxicity occurred in this animal.…”
Section: Discussionmentioning
confidence: 86%
“…Algumas espécies tendem a tolerar uma vasta gama de condições ambientais (Rubbo & Kiesecker 2005), enquanto espécies restritas a um ambiente ou conjunto de condições específicos tendem a ter mais dificuldade em manter populações viáveis em áreas alteradas por ação antrópica (Lips et al 2003 Industrial apresentam a) redução na condição corporal, evidenciadas por menores índices corpóreos (Jakob et al 1996;Schulte-Hostedde et al 2005;Băncilă et al 2010), b) fígados e rins maiores em resposta ao aumento metabólico gerado pelo trabalho de detoxificação (Williams & Iatropoulos 2002;Arrieta et al 2004), c) gônadas menores como evidência de redução na capacidade reprodutiva (Rie et al 2005), d) corpos gordurosos menores devido a alterações na fisiologia e no metabolismo do indivíduo, levando a possível redução no investimento em reprodução (Dundappa & Saidapur 1992;Langerveld et al 2009), e) redução na imunocompetência e consequente maior quantidade de parasitas (Carey et al 1999;Linzey et al 2003;Rohr et al 2008;Rollins-Smith et al 2011), f) baços menores devido à redução na proliferação de células nesse órgão causada pela contaminação, evidenciando redução na imunocompetencia (Christin et al 2003;Linzey et al 2003), e g) maior quantidade de contaminantes nos tecidos. Klumpp et al 1996Klumpp et al , 1998Klumpp et al , 2000Klumpp et al , 2002Furlan et al 1999;Gonçalves et al 2000;Mayer et al 2000aMayer et al , 2000bMoraes et al 2000Moraes et al , 2002Szabo et al 2003;Schoenlein-crusius et al 2006).…”
Section: Introductionunclassified